Hookworm in Stray Cats (Felis silvestris catus) as Cutaneous Larva Migrant Agent (CLM) in Humans - Mahendra, Fadhil Ihsan; Soebaktiningsih, Soebaktiningsih; Prabawati, Risma Karlina (Folia Medica Indonesiana, 2022)
Highlights : • Risk factors that can increase the incidence of CLM in humans include male sex, children aged <15 years, low-income people, and daily behaviour of walking outdoors without using footwear, especially on the sand. • Risk factors that play the most role in increasing the incidence of CLM in humans are walking outdoors without using footwear, especially on the sand. Abstract : Cats arethe host of a wide variety of microorganisms including ectoparasites and endoparasites.One of theendoparasites that infect cats is hookworm. The hookworms consists of two groups, the animal hookworms, and the human hookworms. The manifestation that can be caused by animal hookworms to humans is Cutaneous Larva Migrant (CLM). This study aimed to discover whether hookworm in stray cats (Felis silvestris catus) can cause CLM in humans. We performed a systematic search in Pubmed/Medline and Cochrane published between 2016 and 2021 with no restrictions by language, research country, or type of research design . The results of the analysis showed that the high level of hookworms infection in stray cats could increase the risk of CLM in humans. Based on the study, we could conclude that the high prevalence of hookworm infection in cats plays an important role in the increased risk of zoonoses in humans which in turn could also increase the prevalence of CLM in humans.